Prevalence of ectoparasites in guinea pigs (Cavia porcellus) of family-commercial breeding in the district of Matahuasi, Junín (Peru) - Santos R., Fiorela (2020)
The aim of this study was to determine the prevalence of ectoparasites in guinea pigs (Cavia porcellus) of family-commercial breeding in the district of Matahuasi, Junín, Peru, as well as to identify parasitic species, type of parasitic association and evaluate the association between the presence of ectoparasites and the productive stage and sex variables. A total of 299 guinea pigs were evaluated between January and March 2017. Ectoparasites were collected using four techniques (deep skin scraping, adhesive tape, trichogram and fine combing). The ectoparasites were examined by direct observation under the microscope at 10X and 40X, and in some cases they were rinsed with 10% KOH. The prevalence of ectoparasites was 67.0 ± 5.3%, identifying three species of acariforms (63.0 ± 5.5%) and one species of Phthiraptera (12.0 ± 3.7%). Among the acariforms, Ornithonyssus bursa (53%), Chirodiscoides caviae (15%) and Dermanyssus gallinae (7%) were identified. The Phthiraptera species was Gliricola porcelli (12%). Monoparasitism was the most frequent (75%). No significant association was found between the presence of ectoparasites and the productive stage and sex variables.